43.1: Invited Paper: Demonstrating Ideal Injection Efficiency & Enabling Cost Effective Manufacturing with Solution Processed Hole Injection Layers. Issue 1 (1st July 2013) - Mathai, Mathew; Seshadri, Venkataramanan; Chopra, Neetu; Scott, Eli; Brown, Christopher; Woodworth, Brian; Muehlbauer, John; Zhang, Hongmei; Benson‐Smith, Jessica; Wang, Jian; Li, Sergey; Gowrisanker, Srinivas; et al.
Abstract Latest developments in solution processed hole injection layer (HIL) technology that has enabled near‐ohmic injection into OLED stacks will be presented. Some of the advantages inherent to solution processing will be demonstrated including the planarization of low cost engineered OLED substrates.